PENTINGNYA WAWASAN JURNALISTIK PENDIDIKAN BAGI GURU DAN DOSEN DALAM ERA GLOBAL - Anis Fauzi; Nana Surayapermana; Eni Nur’aeni (Jurnal Inovasi Penelitian, 2022)
This paper discusses the need for the teaching profession and lecturers to understand, master and develop the concept of educational journalism while carrying out their main duties as professional educators in schools and campuses. Through an understanding of the concept of educational journalism, it is hoped that teachers and lecturers will be able to create an active and dynamic learning atmosphere by making creative writings published in national mass media as well as regional ang local mass media. Writing in the mass media shows that teachers and lecturers are creative, so that students or students are motivated to read the writings of teachers or lecturers ideally. By understanding educational journalism insight, a teacher can write in the form of features, articles and essays that can be published in local, regional and national mass media. By understanding educational journalism insight, a lecturer can write scientific papers published in unaccredited national journals, Sinta accredited national journals and indexted international journals. A teacher or a lecturer who feels serious about wanting to became a writer, must have the courage to saya “ I write, that’s why I exist”.